Respuesta :
Answer:
y = 3
y = 2
y = 1
y = 0
Step-by-step explanation:
Given expression;
y = (-x/3) + 2
Find:
Value of y, if x = -3
Value of y, if x = 0
Value of y, if x = 3
Value of y, if x = 6
Computation:
Value of y, if x = -3
y = (-x/3) + 2
y = (3/3) + 2
y = 3
Value of y, if x = 0
y = (-x/3) + 2
y = (-0/3) + 2
y = 2
Value of y, if x = 3
y = (-x/3) + 2
y = (-3/3) + 2
y = 1
Value of y, if x = 6
y = (-x/3) + 2
y = (-6/3) + 2
y = 0
----------------------------------------------------------------------------------------------------------------
Hope it helps :)
Can I please get brainliest
Answer:
x = -6, -3, 0, 3, 6
y = 4, 3, 2, 1, 0
Step-by-step explanation:
Input the different values of 6 into the equation: y = -x/3 + 2
When x = -3
- y = -(-3)/3 + 2
- y = 3/3 + 2
- y = 1 + 2
- y = 3
When x = 0
- y = -(0)/3 + 2
- y = 0/3 + 2
- y = 0 + 2
- y = 2
When x = 3
- y = -(3)/3 + 2
- y = -3/3 + 2
- y = -1 + 2
- y = 1
When x = 6
- y = -(6)/3 + 2
- y = -6/3 + 2
- y = -2 + 2
- y = 0
-Chetan K